(untitled) (World Bulletin of Management and Law, 2022)
Study this aim for knowing influence power pull tour whale shark and activities fisherman to enhancement economy people in the village Botubarani District of Kabila Bone , District of Bone Bolango Gorontalo Province . This study uses a quantitative approach with the ex post facto method. Source of data in study this is primary data through deployment questionnaire to 63 people. Data analysis techniques used is multiple linear regression with SPSS version 21 help . Research results this show that (1) Power pull tour influential whale shark positive and significant to enhancement economy people in the village Botubarani Kabila Bone District , Bone Bolango District Gorontalo Province . Meaning from coefficient positive show that power pull tour whale shark gives good impact _ in reach enhancement economy people in the village Botubarani Kabila Bone District , Bone Bolango District Gorontalo Province . (2) Activities fisherman take effect positive and significant to enhancement economy people in the village Botubarani Kabila Bone District , Bone Bolango District Gorontalo Province . Meaning from coefficient positive show that the more active fisherman in activity the economy so enhancement economy Public will the more good . 3) Power pull tour whale shark and activities fisherman by together take effect significant to enhancement economy people in the village Botubarani Kabila Bone District , Bone Bolango District Gorontalo Province with score coefficient determination by 61.20%. Whereas the rest of 38.80% can explained by other variables outside of this study.